(untitled) (Jurnal Sains Komunikasi dan Pengembangan Masyarakat [JSKPM], 2020)
Institutional agriculture in the village is one of the efforts to develop rural communities. One of the agricultural institutions that play a role is the Farmer Women Group. The purpose of this study is to look at the relationship between group dynamics and institutional sustainability. This research uses quantitative methods approach is carried out by survey using questionnaire instruments while qualitative data is obtained through in-depth interview and observation guidelines. The results of this research show that KWT Pelangi is superior to two elements compared to KWT Sekar Melati includes group structure and group atmosphere, while KWT Sekar Melati is just one element include group cohesiveness and the six other elements both of KWT Sekar Melati and KWT Pelangi are of moderate value. The three elements of institutional sustainability include the sustainability of production, the sustainability of partnership, economic sustainability both of KWT Sekar Melati dan KWT Pelangi are of moderate value. The relationship between group dynamics and institutional sustainability KWT Pelangi has two elements namely the sustainability of partnership and economic sustainability. However, there is one element in KWT Sekar Melati namely economic sustainability. Keywords: Group Dynamics, Farmer Women Group, Institutional SustainabilityÂ ABSTRAK Kelembagaan pertanian di desa menjadi salah satu upaya pembangunan masyarakat perdesaan. Salah satu kelembagaan pertanian yang berperan adalah Kelompok Wanita Tani. Tujuan penelitian ini adalah untuk melihat hubungan antara dinamika kelompok dengan keberlanjutan kelembagaan. Penelitian ini menggunakan metode kuantitatif dilakukan dengan survei dengan menggunakan kuesioner sedangkan data kualitatif didapatkan melalui panduan wawancara mendalam dan observasi. Hasil penelitian ini menunjukkan KWT Pelangi lebih unggul dua unsur dinamika kelompok yakni struktur kelompok dan suasana kelompok, sedangkan KWT Sekar Melati hanya satu unsur yakni kekompakan kelompok, enam unsur lainnya baik KWT Sekar Melati maupun KWT Pelangi sama-sama bernilai sedang. Ketiga unsur keberlanjutan kelembagaan meliputi keberlanjutan produksi, keberlanjutan kemitraan, dan keberlanjutan ekonomi baik KWT Sekar Melati maupun KWT Pelangi sama-sama bernilai sedang. Adapun hubungan antara dinamika kelompok dengan keberlanjutan kelembagaan pada KWT Pelangi terdapat dua unsur yakni keberlanjutan kemitraan dan keberlanjutan ekonomi. Namun, pada KWT Sekar Melati hanya terdapat satu unsur yakni keberlanjutan ekonomi Kata Kunci: Dinamika Kelompok, Kelompok Wanita Tani, Keberlanjutan Kelembagaan Â